COMPARISON OF THE METHOD OF ELECTROMETRIC DETERMINATION OF ROOT CANAL PARAMETERS AND THE METHOD OF THRESHOLD SEGMENTATION OF RADIOGRAPHS - Oleksii Perepelytsia; Oleg Avrunin (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article is X-ray images of teeth during endodontic operations. The goal of the work is to compare the developed method of segmentation of the radiograph to determine the length of the root canal with the electrometric and mathematical methods in practice. The article uses the following methods: principles of endodontic preparation of teeth; methods of determining the working length of the root canal (radiological, electrometric); threshold segmentation method; method of segmentation of bone structures on tomographic images. The following results were obtained: the existing methods of determining the working length of the root canal were analyzed, the main advantages and disadvantages of each method were highlighted. The mathematical method is fast, but inaccurate and can only serve as a preliminary estimate. Electrometric is the most accurate, but has very strict requirements for measurement in the area of canal moisture, as well as invasiveness of the method has a number of disadvantages. Radiological is the most promising for research because of its painlessness to the patient, low radiation dose during intraoral radiography and the possibility of using image processing algorithms to refine the measurement results. This work formulated principles for segmentation and extraction of tooth contours on the X-ray image to determine working length and conducted practical studies to compare all methods of analysis. Conclusions. The application of the electrometric length determination method gives the most accurate result, but the segmentation of the radiograph allows the doctor to obtain additional information about the architectonics of the root canal. As well as the possibility of using image processing such as segmentation, contour extraction and automatic determination of the apical constriction zone make this method the most perspective. The most optimal is the combination of these two methods in practice, which requires additional research.